Data for entering the strong coupling regime in conventional organic solar cells - Börjesson, Karl (University of Gothenburg, 2025)
The raw data for figures in the article "Entering the strong coupling regime in conventional organic solar cells" av Nicola Peruffo, Runwan Chen, Dongyan Li, Qinghe Wu, och Karl Börjesson are here stored. The naming of files follows the Figure numbering in the article.

Rådata till figurer i artikeln "Entering the strong coupling regime in conventional organic solar cells" av Nicola Peruffo, Runwan Chen, Dongyan Li, Qinghe Wu, och Karl Börjesson finns här lagrade. Numreringen av filer följer numreringen av figurer i artikeln.
Data for entering the strong coupling regime in conventional organic solar cells
Keywords: organic electronics; organisk elektronik; spectroscopic analysis; Chemical Sciences; Kemi; Physical Chemistry; Fysikalisk kemi; Materials Chemistry; Materialkemi